Analisis Persiapan Persiapan Implementasi PSAK 74 pada Perusahaan Asuransi Indonesia (Studi Kasus pada Perusahaan Asuransi X) - Fitri Anjani; Ludovicus Sensi Wondabio (Politeknik Ganesha Medan, 2023)
Abstract The importance of the insurance industry for the economy, the establishment of accounting standards in the financial statements of insurance companies is needed to support the improvement of corporate governance. Until now, the preparation of financial reports for insurance companies in Indonesia still follows the standards of Statement of Financial Accounting Standards (PSAK) 62 concerning Insurance Contracts which is a temporary standard, so a new, better standard is needed, namely PSAK 74 which is an adoption of IFRS 17 and will become effective internationally on January 1, 202s3, while in Indonesia it will become effective on January 1, 2025. This study aims to determine the readiness of insurance companies in implementing PSAK 74, its impact on the presentation of financial statements, and to find out the issue of gaps that occur in the implementation PSAK 74. This research is a qualitative case study with primary and secondary data taken through semi-structured interview techniques, observation and documentation. From the research results, it was found that Insurance Company X had started to make preparations for the implementation of PSAK 74, but there were still gaps related to several issues that must be considered in its implementation. Meanwhile, the presentation of the financial statements themselves did not experience significant changes except for adjustments to several accounts related to the implementation of PSAK 74.